Digital technologies for promotion of healthy eating habits in teenagers - Caroline Magalhães de Alcântara; Amanda Newle Sousa Silva; Patrícia Neyva da Costa Pinheiro; Maria Veraci Oliveira Queiroz (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: Identify and analyze the scientific literature on digital technologies for promotion of healthy eating habits in teenagers. Method: Integrative review of articles published in English and Spanish, available in full on four databases. The descriptors used were (Adolescent health) OR (Teen health) AND (Healthy diet) OR (Healthy eating) AND (Educational technology) OR (Instructional technology), respectively, from which eight articles were selected. Results: Among the studies included, three were digital games; two web-based nutrition interventions; two using online programs to prevent obesity; and one nutritional advice using multimedia. They showed experiences of digital technology and its effects on knowledge improvement and/or behavior of participants when developing healthy eating habits. Conclusion: Digital technologies are innovative tools present in the lives of teenagers, with the possibility of being used for education and promotion of healthy eating, contributing to the empowerment of the subject for his/her self-care.